Evaluation of human-centered pedaling in the city of Galogah - sadegh seidbeigi; omeid samandari; ali hossein shahein; mosttafa behshad (تحقیقات کاربردی علوم جغرافیایی)
The increasing population growth in urban areas has created adverse social, economic, environmental and physical impacts on cities. Therefore, cities must provide better places for life. One of these places is the creation of pedestrian streets. The purpose of this research is to find out the development of a pedestrian with a human-centered approach in the city of Golghah which has been selected in the direction of three streets of Imam, 17 Shahrivar and Taleghani. In this study, we evaluated the factors influencing the utility of urban walkways in a human-centered approach from the point of view of experts and people. So this chapter consists of three main sections. In the first part of the criteria, in the form of a questionnaire and 348 questionnaires, pedestrians and residents were evaluated on the status of the streets in view of these criteria and indicators to determine the best option for walking. In the following, the criteria and indicators extracted from the study of theoretical foundations and research literature were ranked by Delphi method and the hierarchical analysis model using expert selection software. Finally, considering the importance of each indicator and prioritizing people in the streets, according to descriptive studies, alternative strategies are to be prioritized for pedestrians. To do this, first, prioritize alternatives based on the following indicators Then, considering the coefficient of importance of each and the impact of each of these indicators and sub-indicators, prioritizing the streets for the implementation of the human-made walkways was presented that Imam Street with a score of 36% compared to the other highest priority in the city of Haloogha for the implementation of the pedestrian It has a way. As well as Shahrivar St. with 33.4 percent in the next priority for the implementation of the human-like pavement plan. September 17th, with a score of 7.30%, is the third priority for pedestrians.